Curcumin as adjuvant therapy to Meloxicam in treatment of patients with knee Osteoarthritis; Evaluation of antioxidant activity - Maiss Saadi Baqer; Mohammed Mahmood Mohammed; Nizar Abdullateef Jassim (College of Pharmacy / Mustansiriyah University, 2020)
Osteoarthritis (OA) is a chronic degenerative joint disease that doubled in prevalence since the mid of 20th century most commonly due to obesity and aging. Osteoarthritis can affect any joint in the body. The pathogenesis of OA is multifactorial influenced by range of biochemical and mechanical factors.  Oxidative stress is described to play an important role in many diseases including OA. Accumulating evidences suggested the beneficial effect of anti-oxidants for reducing OA severity. Curcumin is a well-known antioxidant agent that acts by different mechanisms in modulating oxidative stress status. This study was designed to evaluate the antioxidant effect of curcumin as adjuvent therapy to a non-steroidal anti-inflammatory drug, meloxicam, in the management of knee osteoarthritis. This prospective open-labelled randomized controlled study was carried out on forty-two eligible patients who were allocated in two groups, serum superoxide dismutase 3 (SOD3) and glutathione reductase (GR) were measured at baseline and after 3 months of the study. Pain and physical function assessment were evaluated by oxford knee score (OKS). Results illustrated highly significant improvement in pain and physical function scores when curcumin used as adjuvant to meloxicam, also curcumin supplementation resulted in significant increase in SOD3 serum level and only a modest decrease in GR serum level when compared to meloxicam alone. In conclusion, this study demonstrated benefit of curcumin when used in combination with meloxicam over using meloxicam alone in modulating antioxidant parameters in blood, in addition to significantly improving pain and physical function after 3 months of treatment.